Let x , y be positive reals such that x + y = 2 , find the maximum value of x 3 y 3 ( x 3 + y 3 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A nice solution. Congratulation. Up voted.
" The maximum of the function is when f '(x) = 0." It can also be minimum?
Log in to reply
Yes, thanks for pointing it out. I've edited it now to say it is the maximum becuase it is a negative quadratic.
f ( x ) = x 3 ∗ ( 2 − x ) 3 ∗ ( x 3 + ( 2 − x ) 3 ) . ∴ f ′ ( x ) = f ( x ) { x 3 3 x 2 − ( 2 − x ) 3 3 ( 2 − x ) 2 + x 3 + ( 2 − x ) 3 3 x 2 − 3 ( 2 − x ) 2 } = 0 . ∴ f ′ ( x ) = 3 ∗ f ( x ) ∗ { x 1 − 2 − x 1 + − 6 x 2 + 1 2 x − 8 4 − 4 x } = 0 ∴ f ′ ( x ) = 3 ∗ f ( x ) ∗ { x ( 2 − x ) 1 − 3 x 2 − 6 x + 4 1 } ∗ { 2 − 2 x } = 0 Since x,y>0, for minimum value 0f the function is x=0, x=1 is maximum. ∴ f ( x ) = 1 ∗ 1 ∗ ( 1 + 1 ) = 2
When using a calculus approach, you should be careful to cover all bases
You need to prove that it's a maximum value.
Thanks . I will see to it. In this problem, second derivative is very complicated. Any suggestion for a better approach ?
Log in to reply
Nope. It's going to be tedious. Best approach is via AM GM.
Seriously you are using calculus on this!!!!!!
G i v e n t h a t x + y = 2 U s i n g t h e A M G M I n e q u a l i t y 2 x + y ≥ 2 x y ⇛ 1 ≥ x y H e n c e t h e m a x i m u m V a l u e o f x y i s 1 . N o w b y s i m p l i f y i n g ( x 3 y 3 ) ( x 3 + y 3 ) W e g e t ( x y ) 3 ( x + y ) ( x 2 + y 2 − x y ) ⇛ ( x y ) 3 ( x + y ) [ ( x + y ) 2 − 3 x y ] N o w p u t t i n g t h e v a l u e s i n t h e e q u a t i o n w e g e t ( x 3 y 3 ) ( x 3 + y 3 ) = 2
This solution is incorrect. It ignores the impact of − 3 x y .
Great. Up voted.
Log in to reply
Either many have got luck or many have talents, this INMO problem has now become level 1!
Why the max of the final expression is obtain when xy is at max? The term -3xy seems to have a negative impact.
Log in to reply
That is right. Though the answer is right but I don't think that the process is proper.
x 3 y 3 ( x 3 + y 3 )
= ( x y ) 3 ( x + y ) ( x 2 − x y + y 2 )
= ( x y ) 3 ⋅ 2 ⋅ ( 4 − 3 x y )
Applying the AM-GM,we have:
( x y ) ⋅ ( x y ) ⋅ ( x y ) ⋅ ( 4 − 3 x y ) ≤ ( 4 x y + x y + x y + 4 − 3 x y ) ) 4 =1
Then x 3 y 3 ( x 3 + y 3 ) ≤ 2 ⋅ 1 = 2
In all the solution they have found greatest value of xy. All have ignored -3xy has a negative impact, to make the product greatest. I don't think that the process is correct.
I have a better solution.
x+y=2=>x=1+k and y=1-k
So the expression becomes
2-2k⁴(3k⁴-8k²+6), after substitution.
Now, k is positive. Also 3k⁴-8k²+6 can be considered as a quadratic polynomial, if k²=p. It's lowest value is 0.666... (using the method of completing the square). Hence the maximum value of expression is when k=0. At that value of k the value of the expression is 2, which is it's maximum value.
@Susant Rautray , we really liked your comment, and have converted it into a solution. If you subscribe to this solution, you will receive notifications about future comments.
Thanks a lot!!! How can I subscribe to comments ?
Log in to reply
If you're using Brilliant on the computer, then the "subscribe" button is next to the Edit button at the bottom left corner.
Given that x+y=2 for maximum value apply AM greter than GM then we get xy=1 substituting in equation( xy^3 )(x^3+y^3)= 1×(x+y)(x^2+y^2 -xy )=1×2×((x+y)^2)-3xy)=1×2×(4-3)=2 So answer is 2
This solution is incorrect. It ignores the impact of − 3 x y .
Take cube both sides then put the value that is give u have equation (8-6x³y³)x³y³, if we put the value of x and y =1then we easily get the ans.
Problem Loading...
Note Loading...
Set Loading...
We can simplify the function:
x 3 y 3 ( x 3 + y 3 )
= ( x y ) 3 ( x + y ) ( x 2 − x y + y 2 )
= ( x y ) 3 ( x + y ) ( ( x + y ) 2 − 3 x y )
We know from the question that x + y = 2 :
= ( x y ) 3 ⋅ 2 ⋅ ( 4 − 3 x y )
= ( x y ) 3 ⋅ ( 8 − 6 x y )
x + y = 2 ⇒ y = 2 − x
Hence we can write the function x y as x ( 2 − x ) = 2 − x 2
f ( x ) = 2 − x 2 ⇒ The maximum of the function is when f ′ ( x ) = 0 because it is a negative quadratic
f ′ ( x ) = 2 − 2 x = 0 ⇒ Hence the maximum value of the function is when x = 1
So the maximum value of the function = x y = 1 ( 2 − 1 ) = 1
We can now substitute the maximum into the original equation:
( 1 ) 3 ⋅ ( 8 − 6 ( 1 ) )
= 1 ⋅ 2
= 2
So 2 is the maximum value of the function.